2017
DOI: 10.1021/acssuschemeng.7b00204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heavy Metal (Zn) on Redox Property of Hydrochar Produced from Lignin, Cellulose, and d-Xylose

Abstract: To provide fundamental information for environmentally sound utilization of hyperaccumulator, hydrothermal carbonization (HTC) of Zn-loaded lignin, cellulose, and D-xylose was carried out to explore the effect of Zn(II) on chemical structure and the redox property of hydrochar. By batch redox reaction as well as I 2 /NaBH 4 titration, we quantified the reducing and oxidizing capacities of three kinds of hydrochar. Results indicated that all hydrochar samples are redox-active with a reducing ability that is mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…While the data suggest cellulose contributed to the ESCs of wood pyrolyzed hydrochars, the fact that cellulose pyrolyzed hydrochars possessed lower ESCs than wood pyrolyzed hydrochars for the same pyrolysis temperature (Figure ) indicates that other wood components (e.g., lignin) contributed more than cellulose to the total ESCs of wood pyrolyzed hydrochars on the mass basis. It has been suggested that lignin-derived chars possessed twice the number of (hydro)­quinoic functional groups than cellulose- and d -xylose-derived chars, which is consistent with the observation from this study.…”
Section: Resultssupporting
confidence: 92%
“…While the data suggest cellulose contributed to the ESCs of wood pyrolyzed hydrochars, the fact that cellulose pyrolyzed hydrochars possessed lower ESCs than wood pyrolyzed hydrochars for the same pyrolysis temperature (Figure ) indicates that other wood components (e.g., lignin) contributed more than cellulose to the total ESCs of wood pyrolyzed hydrochars on the mass basis. It has been suggested that lignin-derived chars possessed twice the number of (hydro)­quinoic functional groups than cellulose- and d -xylose-derived chars, which is consistent with the observation from this study.…”
Section: Resultssupporting
confidence: 92%
“…However, PH had higher peaks for the redox property compared to the other hydrochars, while it did not promote methane production. The redox properties of hydrochar were further quantified by I 2 /NaBH 4 titration (Figure 5b), 17 and PH still had the highest redox capacity considering the highest electron donating capacity (EDC) and electron accepting capacity (EAC), which was consistent with cyclic voltammetry (CV) results. It seems that the redox properties of hydrochar were also not correlated to the enhancement of the methane production rate.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
“…However, a detailed mechanism is still unknown, especially from the microbial aspects. Although there is still no literature reporting the conductivity of hydrochar, it is known that hydrochar has redox-active properties . Previous studies showed that biochar could facilitate DIET for microbial reduction of ferrihydrite and methanogenesis due to its redox-active properties. , Therefore, it was hypothesized that hydrochar could promote methanogenesis through DIET.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the formation of stable coordination compounds between phenolic hydroxyl groups within lignin and Zn ions can produce a robust and tight layer on the Zn metal surface. 26 Secondly, oxygen-containing functional groups within lignin can also coordinate with empty orbitals within Zn metal to form coordinate bonds, 27 which can improve the adhesive forces on the surface of Zn metal. Lastly, lignin coated lms play a role as a block layer to homogenize the interfacial Zn 2+ ux and suppress the formation of Zn dendrites and the corrosion of I 3 À ions.…”
Section: Introductionmentioning
confidence: 99%